Capacity Utilization and Production Function Estimation in Postwar American Manufacturing - Lovell, C. A. Knox (Quarterly Journal of Economics, 1968)
I. Introduction, 219. — II. The transcendental production function, 221. — III. An empirical test of the transcendental production function, 228. — IV. Conclusions, 237. — Appendix, 238.